Bridging the Knowledge–Practice Gap in Dengue Prevention: A Descriptive Analysis of Community Behavior - Erikayani, Ni Kadek Virna; Oktaviani, Putu Wiwik; Abadi, Moh. Fairuz (Future Science, 2025)
Introduction: Dengue hemorrhagic fever (DHF) in Indonesia is still a serious concern in the world, especially in endemic areas. This disease arises and is transmitted from the Dengue virus through the bite of the Aedes Aegypti mosquito, which can be suffered from toddlers to adults. If not treated immediately, it can lead to death. The government is promoting a mosquito nest eradication program through the 5M movement (draining, covering, burying, replacing water, and sprinkling larvicide powder) as a key preventive measure in reducing the spread of Aedes aegypti mosquitoes that depend on community behavior. Objective: This study aims to find out the picture of community behavior in Mosquito Nest Eradication (5M) as an effort to prevent dengue fever in Banjar Tengkulak Kaja Kauh, the working area of the Regional Technical Implementation Unit of the Sukawati I Health Center. Methods: The research was quantitative descriptive with a simple random sampling technique and involved 175 samples. Data was collected using questionnaires that have been tested for validity and reliability Results: The results showed that the majority of respondents were categorized as having fair behavior, as many as 112 respondents (64%), 53 respondents (30.3%) had good behavior, and 10 respondents (5.7%) had poor behavior. Conclusion: Most of the community's behavior was found to be in a fair category, which shows that although the community's knowledge and attitudes are relatively good, there is still a gap in the implementation of the action, so sustainable programs and social support are needed to increase the active participation of the community in the eradication of mosquito nests.